Asthma and COVID‐19 in children: A systematic review and call for data - Castro‐Rodriguez, Jose A.; Forno, Erick (Pediatric pulmonology, 2020)
Rationale Whether asthma constitutes a risk factor for coronavirus disease‐2019 (COVID‐19) is unclear. Here, we aimed to assess whether asthma, the most common chronic disease in children, is associated with higher COVID‐19 risk or severity in pediatric populations. Methods We performed a systematic literature search in three stages: first, we reviewed PubMed, EMBASE, and CINAHL for systematic reviews of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and COVID‐19 in pediatric populations, and reviewed their primary articles; second, we searched PubMed for studies on COVID‐19 or SARS‐CoV‐2 and asthma/wheeze, and evaluated whether the resulting studies included pediatric populations; third, we repeated the second search in BioRxiv.org and MedRxiv.org to find pre‐prints that may have information on pediatric asthma. Results In the first search, eight systematic reviews were found, of which five were done in pediatric populations; none of the 67 primary studies included data on pediatric asthma as a comorbidity for COVID‐19. In the second search, we found 34 results in PubMed, of which five reported asthma in adults, but none included data on children. In the third search, 25 pre‐prints in MedRxiv included data on asthma, but none on children. We found one report by the US Centers for Disease Control and Prevention stating that 40/345 (~11.5%) children with data on chronic conditions had “chronic lung diseases including asthma,” and one from a tertiary hospital in New York that reported asthma in 11/46 (~23.9%) children hospitalized for COVID‐19. Conclusion There is scarcely any data on whether childhood asthma (or other pediatric respiratory diseases) constitute risk factors for SARS‐CoV‐2 infection or COVID‐19 severity. Studies are needed that go beyond counting the number of cases in the pediatric age range.